Islamic Spiritual Guidance as a Medium to Foster Motivation to Recover in Residents (Utilization of Information Technology as an Administrative Tool) (Proceeding of Dakwah Saizu International Conference, 2023)
The smuggling of illegal drugs or NARCOTICS is currently growing rapidly, especially with the level of supervision and guarding of trade routes that are not well monitored and running well, thus making the development of these illegal drugs uncontrollable. The media that are commonly used in Islamic spiritual guidance as a form of service provided to residents by the Sentra Satria Baturaden can be carried out individually or in groups. As with the current use of technology, using digital technology or the internet can make it easier and seem more effective and efficient, on the other hand, with the television provided by the Sentra, it can be used to provide studies in digital form. This research uses a descriptive qualitative method, which will discuss or examine the phenomenon or problem that will be discussed in more detail and detail. Utilization of addiction counseling analysis will also indirectly bring counselors closer to the main problems of resident drug users. The techniques used in this study were direct observation of residents and direct interviews. The purpose of this research is to utilize Islamic spiritual guidance media in fostering motivation to recover in methamphetamine-using residents.